0 | 0 |
Propositional Algebra
|
1 | 1 |
=====================
|
2 | |
|
3 | |
_NOTE: still under development_
|
4 | 2 |
|
5 | 3 |
This is a possible formulation of propositional algebra in Eqthy. For some background,
|
6 | 4 |
see Section II of [An Algebraic Introduction to Mathematical Logic][] (Barnes and Mack, 1975)
|
|
31 | 29 |
|
32 | 30 |
axiom (#MP) th(P, th(impl(P, Q), e)) = th(Q, e)
|
33 | 31 |
|
|
32 |
(And, for convenience, a reversed version of it. FIXME make this work with #th-comm)
|
|
33 |
|
|
34 |
axiom (#MP-rev) th(impl(P, Q), th(P, e)) = th(Q, e)
|
|
35 |
|
34 | 36 |
I believe this should work. So, let's pick a simple proof and write it up and see if
|
35 | 37 |
the `eqthy` checker can confirm it. Example 4.5 on page 16 of Barnes and Mack:
|
36 | 38 |
|
|
40 | 42 |
set of theorems which contains this theorem.
|
41 | 43 |
|
42 | 44 |
theorem
|
43 | |
// th(X, e) = th(X, th(impl(P, P), e))
|
44 | |
th(X, e) = th(X, th(impl(P, impl(impl(P, P), P)), e))
|
|
45 |
th(X, e) = th(X, th(impl(P, P), e))
|
45 | 46 |
|
46 | 47 |
The proof given in the book is
|
47 | 48 |
|
|
59 | 60 |
th(X, e) = th(X, th(impl(P, impl(impl(P, P), P)), e)) [by substitution of impl(P, P) into Q]
|
60 | 61 |
|
61 | 62 |
th(X, e) = th(X, th(impl(P, impl(impl(P, P), P)),
|
62 | |
th(impl(impl(P, impl(Q, R)), impl(impl(P, Q), impl(P, R))), e)))
|
63 | |
[by #A2]
|
|
63 |
th(impl(impl(P, impl(Q, R)), impl(impl(P, Q), impl(P, R))), e))) [by #A2]
|
64 | 64 |
|
65 | 65 |
th(X, e) = th(X, th(impl(P, impl(impl(P, P), P)),
|
66 | 66 |
th(impl(impl(P, impl(impl(P, P), R)), impl(impl(P, impl(P, P)), impl(P, R))), e)))
|
|
74 | 74 |
th(impl(impl(P, impl(impl(P, P), P)), impl(impl(P, impl(P, P)), impl(P, P))), e)))
|
75 | 75 |
[by substitution of P into R]
|
76 | 76 |
|
77 | |
th(X, e) = th(X, th(impl(impl(P, impl(P, P)), impl(P, P)), e))
|
78 | |
[by #MP]
|
79 | |
// FIXME TODO
|
|
77 |
th(X, e) = th(X, th(impl(impl(P, impl(P, P)), impl(P, P)), e)) [by #MP]
|
|
78 |
|
|
79 |
th(X, e) = th(X, th(impl(impl(P, impl(P, P)), impl(P, P)), th(impl(P, impl(Q, P)), e))) [by #A1]
|
|
80 |
th(X, e) = th(X, th(impl(impl(P, impl(P, P)), impl(P, P)), th(impl(P, impl(P, P)), e)))
|
|
81 |
[by substitution of P into Q]
|
|
82 |
th(X, e) = th(X, th(impl(P, P), e)) [by #MP-rev]
|
80 | 83 |
qed
|
81 | 84 |
|
82 | 85 |
[An Algebraic Introduction to Mathematical Logic]: https://archive.org/details/algebraicintrodu00barn_0
|